The Effect of Price Perception, Service Quality and Ease of Transaction on Commuter Train Ticket Purchasing Decisions (Study on Commuter Line Dhoho Train Passengers at Wonokromo Station) - Rivayanti, Tesa Putri; Soebiantoro, Ugy; Mandasari, Virginia (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims were to determine the effect of price perceptions, service quality, and ease of transactions on purchasing decisions for commuter line train tickets at Wonokromo station. This research uses a quantitative approach. The sampling technique is non-probability sampling using purposive sampling method with a total of 200 respondents. The data analysis method uses Partial Least Squares (PLS) - Structural Equation Modeling (SEM) using the SmartPLS 4.0 software analysis tool. The analysis was carried out through three stages of testing: outer model (validity and reliability test), inner model, and hypothesis testing. The results showed that (1) perceived price has a positive and insignificant effect on purchasing decisions, (2) service quality has a positive and significant effect on purchasing decisions, and (3) ease of transactions has a positive and significant effect on purchasing decisions.